The Concept of Ontological Security in International Political Discourse - A. V. Khudaykulova (MGIMO University Press, 2019)
The article studies “ontological” security concept. In a general sense the term depicts expectations of a state about its stable and predictable relations with counterparts. With the term gaining theoretical sway in constructivism since the 21st century, we argue, that it still lacks instrumental definition with fixed assumptions and variables. The analysis of ontological security is conducted in twofold manner. First, we overview the broad range of interpretations, demonstrate the absence of an instrumental definition of the concept and suggest some parameters of such a definition. Secondly, we study the ways how a state can gain ontological security. Three options of achieving ontological security are being presented: adaptation (assuming the role of ‘another’ from the external environment); change of rules (imposing its own role on the subject with whom the interaction occurs); and the breach of relations. At all these stages, the state tries either to adopt the norms and practices by which it interacts with the environment, or to redefine its position in ongoing relations with counterparties. We conclude by presenting a sought definition of the term and by arguing that the concept enhances the constructivist contribution to the IR theory since it allows to define the logic of states’ behavior in international arena. Thus, states seek to be socialized into an intersubjective reality and to define norms, practices and status through forging common and communicative knowledge with ‘other’. Otherwise, the state’s behavior could be irrational. Theory emphasizes the need to avoid situations of the ontological security dilemma: the state projects its own, mostly protective reality, which, however, does not provide it with ontological security from the counterparty and could potentially push for further escalation of crisis interactions.Authors declare the absence of conflict of interests.